2017
DOI: 10.1371/journal.pone.0175289
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet (UV-C) inactivation of Enterococcus faecium, Salmonella choleraesuis and Salmonella typhimurium in porcine plasma

Abstract: The objective of this study was to assess the effectiveness of an ultraviolet (UV-C, 254 nm) irradiation system on reducing the load of Salmonella typhimurium (S. typhimurium), Salmonella choleraesuis (S. choleraesuis) resistant to streptomycin and Enterococcus faecium (E. faecium) inoculated in sterile porcine plasma and then subjected to different UV-C irradiation doses (750, 1500, 3000, 6000 and 9000 J/L) using a pilot plant UV-C device working under turbulent flow. Results indicated that UV-C treatment ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…The World Health Organization (WHO) (WHO, 2004) guidelines on viral inactivation and removal procedures intended to assure the viral safety of human blood plasma products establishes that a robust inactivation process should be capable of removing or inactivating at least 4 logs of a wide range of viruses (WHO, 2004). In previous studies, the UV-C irradiation of liquid plasma was able to inactive 4 logs of different bacteria and viruses (Polo et al, 2015;Blázquez et al, 2017Blázquez et al, , 2019 and the present study also demonstrated the lack of transmission of any virus after being UV irradiated at a minimum of 3000 J/L. Therefore, UV-C irradiation complies with the WHO definition of a robust inactivation process.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The World Health Organization (WHO) (WHO, 2004) guidelines on viral inactivation and removal procedures intended to assure the viral safety of human blood plasma products establishes that a robust inactivation process should be capable of removing or inactivating at least 4 logs of a wide range of viruses (WHO, 2004). In previous studies, the UV-C irradiation of liquid plasma was able to inactive 4 logs of different bacteria and viruses (Polo et al, 2015;Blázquez et al, 2017Blázquez et al, , 2019 and the present study also demonstrated the lack of transmission of any virus after being UV irradiated at a minimum of 3000 J/L. Therefore, UV-C irradiation complies with the WHO definition of a robust inactivation process.…”
Section: Discussionsupporting
confidence: 83%
“…Then, the UV-C lamp was switched on and irradiation started. One liter of treated plasma was collected into sterile containers at 3000 and 9000 J/L, as previously described (Blázquez et al, 2017). From the 1-L samples of plasma irradiated at 0 J/L, 3000 J/L and 9000 J/L UV-C, 10 mL were used for intraperitoneal injection in naïve pigs.…”
Section: Plasma Uv-c Irradiationmentioning
confidence: 99%
See 1 more Smart Citation
“…The UV-C reactor system SurePure Turbulator used for the study was designed for opaque liquids, manufactured by SurePure Operation AG (Zug, Switzerland) and is described elsewhere [30]. Briefly, the system consists of a reactor with a stainless-steel inlet and outlet chamber with a stainless steel corrugated spiral tube between the chambers.…”
Section: Settings Of Uv-c Systemmentioning
confidence: 99%
“…In fact, it has been extensively used for disinfection of water, surfaces and food products [23,24]. The inability of UV-C radiation to penetrate opaque liquids can be overcome by introducing adequate turbulence insuring that all of the liquid is exposed to the surface of the UV-C light [25][26][27][28][29][30]. UV-C treatment has been shown to reduce bacterial contamination while not inactivating protein functionality or growth enhancing properties of SDAP [31].…”
Section: Introductionmentioning
confidence: 99%